The Novel Gene tank, a Tumor Suppressor Homolog, Regulates Ethanol Sensitivity in Drosophila. - Devineni, A.V.; Eddison, M.; Heberlein, U. (Journal of Neuroscience, 2013)
In both mammalian and insect models of ethanol intoxication, high doses of ethanol induce motor impairment and eventually sedation. Sensitivity to the sedative effects of ethanol is inversely correlated with risk for alcoholism. However, the genes regulating ethanol sensitivity are largely unknown. Based on a previous genetic screen in Drosophila for ethanol sedation mutants, we identified a novel gene, tank (CG15626), the homolog of the mammalian tumor suppressor EI24/PIG8, which has a strong role in regulating ethanol sedation sensitivity. Genetic and behavioral analyses revealed that tank acts in the adult nervous system to promote ethanol sensitivity. We localized the function of tank in regulating ethanol sensitivity to neurons within the pars intercerebralis that have not been implicated previously in ethanol responses. We show that acutely manipulating the activity of all tank-expressing neurons, or of pars intercerebralis neurons in particular, alters ethanol sensitivity in a sexually dimorphic manner, since neuronal activation enhanced ethanol sedation in males, but not females. Finally, we provide anatomical evidence that tank-expressing neurons form likely synaptic connections with neurons expressing the neural sex determination factor fruitless (fru), which have been implicated recently in the regulation of ethanol sensitivity. We suggest that a functional interaction with fru neurons, many of which are sexually dimorphic, may account for the sex-specific effect induced by activating tank neurons. Overall, we have characterized a novel gene and corresponding set of neurons that regulate ethanol sensitivity in Drosophila.